Estimation of vitamin C human protective dose for acetaminophen toxicity, using acute animal toxicity study - Al-Farras, Mudhaffar I.; Abdul-Razzak, Khalid K.; Yacoub, Mohammed; Hananeh, Wael M. (Kurdistan Journal of Applied Research, 2017)
Acetaminophen (APAP) is the main cause of fulminant hepatic failure. Vitamin C is a natural antioxidant with protective potentials against APAP toxic damage. In this animal study, and after an LD50 determination and selection of suitable lethal dose, the investigation was done to select a proper protective dose of vitamin C against lethal APAP dose. All 6 animal groups received a lethal dose of APAP (3250 mg/kg), group II, III and IV received 500, 1000 and 1500 mg/kg vitamin C respectively, group V received 1200 mg/kg N-Acetylcysteine (NAC), and group VI receive 1000 mg/kg vitamin C and 1200 mg/kg NAC. Mortality was recorded and liver histopathology was carried out. The results showed, the mortality rate in the group I was 68.75% and 37.5%, 31.25% in group II and III respectively, while group IV Showed a higher mortality rate and in group V and VI it was 25%. There was also a gradual reduction in the grade of histopathological damage in all groups, ranging from 2.4 ± 0.55 in group I to 0.4 ± 0.55 in group V and VI. In conclusion, vitamin C showed an increasing reduction in mortality and more histopathological protection, and it was more significant at 1000 mg/kg. NAC adds no more protection or reduction in mortality. The estimated protective dose of vitamin C was 700 to1127 mg for each gram of APAP. Incorporation of this dose of vitamin C with APAP preparations may be considered as a promising method for reducing mortality or severity of APAP intoxication.